The Idea of the Gaining and Deprivation of the Supreme Authority in the Belarusian-Lithuanian Chronicles - Ящук, О. (Київський національний університет імені Тараса Шевченка, 2019)
The article is devoted to the problem of representations of supreme authority in the Belarusian-Lithuanian chronicles through a prism of the notices about the gaining and deprivation of the power of the ruler. The author analyzed the first redaction of the Belarusian-Lithuanian chronicles that containing the "Chronicle of the Grand Dukes of Lithuania", the second redaction that containing the "Chronicle of the Grand Duchy of Lithuania" and the third redaction ("Bychowiec Chronicle"). The study highlighted several ways of the supreme authority's legitimation: by right of establishment, by right of inheritance, by right of conquest, by the acceptance of the local population, by the electoral way, by the coup if the organizers of it belonging to the ruling dynasty. It should be noted that the way of justifying the right to power through to underscores of blood ties and prince's enthronement of the son of the previous ruler or less often brother is the main way of gaining the power in the chronicles. The article gives a detailed analysis of features of the chronicle notices about the coronation of the representatives of the Gediminids dynasty. In addition, the notices about the deprivation of the authority usually as a result of the death of the ruler are investigated in the article. Notices of the death of the ruler in contradistinction to notices about the enthronement are mainly the fact statements. In the most complete form, the notes of the death of the ruler include the information about a long successful reign, facts of the ruler death and information about the birth and enthronement of the successor.

Присвячено проблемі уявлень про верховну владу в пам'ятках білорусько-литовського літописання крізь призму звісток про набуття та позбавлення влади володарем. Проаналізовано білорусько-литовські літописи першого зводу, що містять "Літописець великих князів литовських", другого зводу, що містять "Хроніку Великого князівства Литовського", та третій звід ("Хроніка Биховця"). У результаті дослідження виділено декілька шляхів легітимізації великокнязівської влади: за правом заснування; за правом успадкування; за правом завоювання; шляхом прийняття місцевим населенням; виборним шляхом; шляхом перевороту, у випадку приналежності змовників до правлячого роду. Слід зауважити, що спосіб обґрунтування права на владу через підкреслення кровного зв'язку і вокняжіння (найчастіше сина попереднього правителя, рідше – брата) є основним у літописних текстах. Також здійснено аналіз особливостей літописних повідомлень про коронацію представників роду Гедиміновичів. Крім того, досліджено вміщені в літописах повідомлення про завершення правління (як правило, унаслідок смерті правителя). На відміну від звісток про інтронізацію, звістки про смерть правителя носять переважно характер констатації факту. У найповнішому вигляді звістка про смерть правителя включає наступну інформацію: про довге успішне правління; про власне смерть; інформацію про народження і вокняжіння наступника.
Уявлення щодо набуття та позбавлення верховної влади в білорусько-литовських літописах
Keywords: idea; supreme authority; grand duke; enthronement; death; Grand Duchy of Lithuania; Belarusian-Lithuanian chronicles; уявлення; верховна влада; великий князь; інтронізація; смерть; Велике князівство Литовське; білорусько-литовське літописання